Analysis of Compliance with WCAG Guidelines Regarding Contrast Im-plementation in an E-Learning Quiz - Krzysztof Dziedzic; Marcin Barszcz; Tomasz Wiśniewski (Journal of Computer Sciences Institute)
In the process of distance learning, modern information and educational solutions are increasingly employed. The introduction of tools facilitating compliance with WCAG guidelines to course creators, enhances content accessibility for individuals with disabilities, eliminating barriers to education access. This aligns with the concept of universal design, aiming to create courses and instructional materials accessible to a broad audience, regardless of individual needs, abilities or conditions. While this is a standard in web design, it is often overlooked in distance learning and course de-sign. This paper focuses on analyzing the correctness of implementing a component allowing the assessment of WCAG compliance in designed quizzes using an exercise creator. The implementation was based on the Quizer e-learning plat-form. Quizzes in the field of cybersecurity were designed to meet contrast guidelines according to the WCAG 2.1 stand-ard, followed by user testing. The research results confirmed the correctness of the applied solutions and emphasized the necessity of designing IT tools considering potential disabilities of future users of e-learning quizzes.